2009
DOI: 10.1053/j.gastro.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

α-Fetoprotein, Des-γ Carboxyprothrombin, and Lectin-Bound α-Fetoprotein in Early Hepatocellular Carcinoma

Abstract: Background and Aims-Alpha-fetoprotein (AFP) is widely used as a surveillance test for Hepatocellular carcinoma (HCC) among patients with cirrhosis. Des-gamma carboxy-prothrombin (DCP) and lectin-bound AFP (AFP-L3) are potential surveillance tests for HCC. The aims of this study were to determine performance of DCP and AFP-L3 for the diagnosis of early HCC, whether they complement AFP, and what factors affect DCP, AFP-L3 or AFP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
519
8
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 645 publications
(573 citation statements)
references
References 24 publications
(29 reference statements)
17
519
8
4
Order By: Relevance
“…In patients with high levels of tumor markers, complete resection Nanashima et al, Page 5 or necrosis of HCC should result in normalization of tumor markers within the half life of these markers, only a couple of days (14,16). A few reports, including our preliminary studies, indicated that changes of serum levels of AFP and PIVKA-II correlate with prognosis (14,17,18). However, to date, there is no consensus regarding the value of post-treatment evaluation of tumor markers.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with high levels of tumor markers, complete resection Nanashima et al, Page 5 or necrosis of HCC should result in normalization of tumor markers within the half life of these markers, only a couple of days (14,16). A few reports, including our preliminary studies, indicated that changes of serum levels of AFP and PIVKA-II correlate with prognosis (14,17,18). However, to date, there is no consensus regarding the value of post-treatment evaluation of tumor markers.…”
Section: Introductionmentioning
confidence: 99%
“…Specific HCC markers, such as PIVKA-II or AFP levels, are commonly used in Japan for the diagnosis of HCC or for the evaluation of tumor aggressiveness [19][20][21][22][23]. It has been reported that high values of these preoperative markers reflect the prognosis for HCC patients who undergo hepatectomy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers could be a useful tool to overcome theoretical limitations of US: its evaluation is not subjective, does not depend on the operator and it may be reproducible, as well as it is relatively cheap and a tool easy to access in areas with low monetary income. Regrettably, different tumor markers evaluated in early stage HCC scenario have shown a low diagnostic accuracy (10)(11)(12)(13) and its association with ultrasonography does not improve its performance and increases the cost of screening programs (14). A recent study has proposed a microRNA panel detected in plasma samples for the early diagnosis, but there is a need of external validation of its efficacy (15).…”
Section: Improving Early Diagnosismentioning
confidence: 99%